Six sigma for project managers - Neuendorf, Steve, 1951- (Management Concepts, 2004)
Six Sigma is a collection of ideas and tools that many organizations are using as part of their efforts to improve the quality of their products and services. Six Sigma for Project Managers explores the concepts that project managers need to know to make six sigma work for their organizations.
Keywords: Project management.; Six sigma (Quality control standard); Total quality management.; elektronické knihy; electronic books